Pepper Fruits at Different Ripening Periods Have Potential Phyto-Biochemical and Enzymatic Responses to Irrigation Levels - Ümit Haydar Erol (Journal of Food Quality)
Irrigation significantly affects plant physiology, especially in arid regions, and plays a crucial role in growth and development. Understanding the effects of irrigation on different fruit ripening periods is essential for sustainable agriculture. This study investigates the phyto-biochemical changes and antioxidative responses of C. baccatum to different irrigation levels during fruit ripening. Five irrigation levels (IL), 150% (IL5), 100% (IL4), 75% (IL3, control), 50% (IL2), and 25% (IL1) field capacity (FC), were studied over three ripening periods at 20th, 40th and 60th days after flowering. Significant changes in phytochemical composition, biochemical properties, and antioxidant enzyme activities were observed in response to different irrigation levels. Reduced irrigation levels combined with fruit ripening led to a significant increase in capsaicinoid components, while drought conditions enhanced antioxidant activity by increasing total phenolics and flavonoids. Conversely, MDA, proline, and protein levels increased under drought stress. Excessive irrigation increased biochemical components throughout ripening, while key enzyme activities responded proportionally to drought severity, with no significant effect above control levels. Optimal chemical components were observed at IL4, with IL1 showing the maximum pungency. Most parameters peaked on the 60th day after flowering, highlighting the importance of fruit ripening periods. These results provide valuable insights for refined irrigation strategies, improved physiological resilience, and sustainable yield enhancement.